Topically Administered Macromolecular Heparin Proteoglycans Inhibit Thrombus Growth in Microvascular Anastomoses - Olsson, Eija; Asko-Seljavaara, Sirpa; Lassila, Riitta (Thrombosis and Haemostasis, 2002)
Previously, during blood perfusion over collagen-coated surfaces; soluble or immobilized heparin proteoglycans (HEP-PG) have been shown to block thrombus growth. Our aim was to study the antithrombotic effect of locally applied unfractionated heparin (UFH, 1 mg/ml), or rat mast cell-derived HEP-PG (MW 750 kD, 10 µg/ml) compared with saline in early (10 min) and late (3 days) thrombus formation upon anastomosis of rat common femoral arteries. In both semiquantitative scanning electron microscopy (SEM) and quantitative platelet Indium 111 -labeling HEP-PG inhibited thrombus growth in comparison with saline. At 10 min, the extent of thrombosis (scale 1-4) in SEM followed the order: saline (3.2+/-0.8) > UFH (2.8+/-1.0) > HEP-PG (1.8+/-0.8), and also Indium111-positive platelets (106) accumulated on the anastomosed vessel in the same order 14.2 +/-7.2, 10.3 +/-5.0, and 7.7 +/-3.1 (saline vs. HEP-PG, p = 0.03 and 0.05, respectively). At 3 days all HEP-PGtreated vessels remained patent with only small mural thrombi, whereas 2/7 saline and 1/7 UFH-treated anastomoses occluded and showed more thrombosis overall. We conclude that locally administered HEPPG inhibit arterial thrombus growth in anastomosed small-sized arteries and could prevent thrombotic complications in (micro)vascular surgery and arteriovenous shunts.
Keywords: Thrombosis; platelets; heparin proteoglycans; microvascular surgery